Rationale for the Use of Pirfenidone in Heart Failure With Preserved Ejection Fraction - Graziani, Francesca; Lillo, Rosa; Crea, Filippo (Frontiers in Cardiovascular Medicine, 2021)
Heart failure with preserved ejection fraction (HFpEF) is a major public health problem with growing prevalence and poor outcomes, mainly due to the lack of an effective treatment. HFpEF pathophysiology is heterogeneous and complex. Recently a “new paradigm” has been proposed, suggesting that cardiovascular and non-cardiovascular coexisting comorbidities lead to a systemic inflammatory state, perturbing the physiology of the endothelium and the perivascular environment and engaging molecular pathways that ultimately converge to myocardial fibrosis. If inflammation and fibrosis are the “fil rouge” in the heterogeneous spectrum of HFpEF, anti-fibrotic and anti-inflammatory drugs may have a role in its treatment. Pirfenidone is an orally bioavailable drug with antifibrotic and anti-inflammatory properties already approved for the treatment of idiopathic pulmonary fibrosis. Pirfenidone has been recently tested in animal models of myocardial fibrosis with promising results. Here we will review the rationale underlying the potential therapeutic effect of Pirfenidone in HFpEF.